Preparation and characterisation of 3D nanotemplates for protein crystallisation - Shah,UV; Parambil,JV; Williams,DRM; Hinder,SJ; Heng,J (Powder Technology, 2015)
Heterogeneous template nucleants are gaining pace as a favoured tool for crystallisation of proteins that may be otherwise difficult to crystallise. A systematic understanding on protein-nucleant interactions has to be developed to enable the development of nucleants for a wide spectrum of biological macromolecules. Thorough characterisation of the nucleants is the key starting point to achieve this aim. This report focuses on the method to produce and characterise functionalised 3D nanotemplates with controlled porosity in the range of 3-22. nm and surface chemistry that can vary from highly hydrophilic to highly hydrophobic in nature. BET and TEM are used to study porosity and pore size distribution while contact angle, XPS and zeta potential are used to investigate surface chemistry of the nucleants. These functionalised 3D nanotemplates are hereby reported to produce protein crystals (concanavalin A and catalase) of different habits without changing any other crystallisation parameters other than the surface chemistry of the templates. This emphasises the potential of 3D nanotemplates with well-ordered porosity and chemistry for further development in protein crystallisation experiments.